Investigation of powder flowability at low stresses by DEM modelling. (16th January 2020) - Stavrou, Alexandros Georgios; Hare, Colin; Hassanpour, Ali; Wu, Chuan-Yu
Highlights: The constraint factor is independent of the pre-consolidation stress. Constraint factor increases with interface energy for only non-cohesive powders. Constraint factor decreases with increasing coefficient of particle static friction. Constraint factor increases with coefficient of particle rolling friction. An increase of plastic yield stress causes a reduction of the constraint factor. Abstract: Ball indentation is a technique capable of assessing powder flowability down to very low consolidation stresses (≤1 kPa). With this method, powder flowability is determined by measuring the hardness of a powder bed, which allows the unconfined yield strength to be inferred via the constraint factor. The latter is well established for continuum materials, whereas for particulate systems its dependency on stress level and powder properties is not well defined. This work investigates these factors by simulating the ball indentation method using DEM. The constraint factor is shown to be independent of pre-consolidation stress. Constraint factor generally increases with interface energy for relatively cohesionless powders, though not for cohesive powders. An increase in plastic yield stress leads to a decrease in the constraint factor. Increasing the coefficient of interparticle static friction reduces the constraint factor, while increasing the coefficient of inter-particle rolling friction significantly increases the constraint factor.